Ethnobotanical prospection, and antibacterial activity of medicinal plants of ancestral Awajún use in the peruvian amazon - Alvarado-Ibáñez, Juan (2023)
The Awajún ancestral knowledge on the use of medicinal plants is part of the mysteries hidden in the Peruvian Amazon. The objective of this research was to identify medicinal plants used in Awajún communities and to evaluate their antibacterial activity.  Using an exploratory study by means of a questionnaire to the wise men and native leaders, ethnobotanical knowledge of the Wawás and Tutumberos communities was compiled, 18 different medicinal plants were identified and collected to later obtain 35 ethanolic extracts, which were evaluated on Staphylococus sp. and Escherichia coli, isolated from patients of the Gustavo Lanatta Luján Hospital in the city of Bagua. The in vitro antibacterial evaluation was performed in triplicate using the Kirby-Bauer method, modified for well diffusion, using 20 µl of extract at 100 mg/ml, bacterial suspension of approximately 1.5 x 108 cells/ml and chloramphenicol at 50 mg/ml as positive control. In the antibacterial susceptibility tests, it was found that the extracts presented different degrees of inhibition against the bacteria under study, the most effective being the stems of tampush or caracha and the leaves of verbena cimarrona, against Gram positive and negative bacteria, respectively.  It is concluded that plant extracts of Awajún medicinal plants could be an alternative treatment for persistent infections.